An investigation into the geomorphology of the Hebron Fault, Namibia, using a satellite-derived, high-resolution digital elevation model (DEM) - Salomon, Guy (Department of Geological Sciences, 2020)
The Hebron fault scarp in southern Namibia is 45 km in length with an average height of 5.5 m and a maximum height of 8.9 m. Namibia is a Stable Continental Region (SCR) — a slowly deforming area within a continental plate. The country also has little recorded seismicity with the largest earthquake on the International Seismological Center (ISC) catalogue being MW 5.4. If the Hebron fault scarp was formed in a single event, this would represent a MW 7.3 earthquake. SCRs do occasionally experience large earthquakes, however, the recurrence intervals between these events is much larger than in rapidly deforming areas. Consequently, studying palaeo-earthquakes allows the record of seismicity to be extended and the characteristics of SCR events to be better understood. These studies may help refine the Mmax estimates required for seismic hazard assessment. Previous work on Hebron has been limited to field descriptions and theodolite survey scarp heights. Furthermore, there have been several interpretations of the fault mechanism and number of rupture events. This study produces a high-resolution Digital Elevation Model (DEM) via stereophotogrammetry using pan-sharpened Worldview-3 satellite imagery (0.31 m resolution). The DEM was used for several geomorphological analyses. These included measuring the scarp height at 160 locations along its length, measuring river channel displacements and identifying knickpoints along river profiles. Results indicate that the scarp formed from a normal, dip-slip fault that ruptured in a single event. This scenario would imply a high slip-to-length ratio. A comparison of other SCR fault scarps in the literature was made which shows that Hebrons’ slip-to-length ratio falls within the values found on other SCR faults. This study also discusses the implications of results for seismic hazard assessment in the region. Due a poor seismic record, probabilistic seismic hazard analysis (PSHA) will calculate a low seismic risk for Namibia. As large earthquakes can occur in SCRs, deterministic seismic hazard analysis (DSHA) can be used to inform policy makers of the worst case scenarios.